Self-efficacy and social support of mothers of preterms in neonatal unit - Sarah Rayssa Cordeiro Sales Pinheiro; Fabiane do Amaral Gubert; Mariana Cavalvante Martins; Eveline Pinheiro Beserra; Clarissa Costa Gomes; Marielle Ribeiro Feitosa (Instituto Materno Infantil de Pernambuco, 2023)
Abstract Objectives: to analyze a correlation between self-efficacy and social support of mothers of preterms in early postpartum. Methods: cross-sectional study, carried out with 120 mothers of preterm infants from a Maternity School, from June to September 2018. Sociodemographic, reproductive and scales were used to assess the Maternal Self-Efficacy and Social Support. A descriptive analysis was carried out and the MannWhitney Test, Kruskal Wallis Test and Spearman correlation were applied. Results: there was a positive correlation between self-efficacy, parity (p=0.017), years of schooling (p=0.017) and Social Support (p=0.002). An unexpected finding was a high self-efficacy among mothers up to eight years of schooling, in the countryside of the State and with low income. Conclusion: social support, in all dimensions: material, affective, emotional, information and social interaction, proven to be a predictor of maternal self-efficacy.